1929 Pa. Laws 777-78, No. 329, §§ 1, 4 - (:unkn) unknown (My University, 1929)
Prohibited selling, giving, transferring, or possessing a machine gun. Punishable by fine up to $1,000 and imprisonment by separate or solitary confinement at labor up to 5 years. Also Prohibited using a machine gun during an attempted crime. Punishable by separate and solitary confinement at labor for up to 10 years.
Keywords: MACHINE GUN RESTRICTION